A retrospective cohort study of three wound catheter infusion analgesia regimes after midline laparotomy. Issue 4 (20th January 2022) - Perry, Jonathan; Byth, Karen; Bullingham, Alan
Abstract : Background: Local anesthetic wound infusion catheters are increasingly used postmidline laparotomy to reduce pain and opioid use, however there is little evidence to support any particular infusion regime. Methods: A retrospective cohort study was undertaken of patients after midline laparotomy who had bilateral local anesthetic wound infusion catheters surgically placed. Patients were recruited into 3 cohorts: ropivacaine 0.2% 5–8 mL/hour continuous wound infusion, 10 mL programmed intermittent bolus 2 hourly, 20 mL programmed intermittent bolus 4 hourly. The primary outcome was the maximum daily Numerical Rating Pain Score with movement (dynamic pain score) recorded during first 96 hours postprocedure. Secondary outcomes included the maximum daily resting pain score and opioid utilization. Results: In three cohorts of 70 patients (n=210), the maximum daily dynamic pain score in the intermittent bolus 2-hourly and 4-hourly cohorts was lower when compared with the continuous infusion group over the first 4 postoperative days. The mean difference in maximum daily pain score with respect to the continuous infusion regime was 0.8 (95% CI 0.2 to 1.4) for the intermittent bolus 2-hourly group and 0.6 (95% CI 0.0 to 1.2) for the 4-hourly group. Generalized estimating equation modeling indicates the reduction in dynamic pain score is greatest with the intermittent bolus 2-hourly regime over the first 72 hours postprocedure. The 2-hourly intermittent bolus regime was also associated with lower opioid utilization and local anesthetic exposure. Conclusions: Intermittent wound infusion catheter infusion regimes were associated with lower maximum daily dynamic pain scores, although the magnitude of this change may be of limited clinical significance.